Analisis Efektivitas Penerimaan Pajak Air Tanah Dalam Upaya Meningkatkan Pendapatan Asli Daerah Kabupaten Sumba Timur - Sri Susanti Widyasari; Marini Manukorung; Dwikora Harjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Groundwater Tax is a tax on the extraction and utilization of groundwater. The phenomenon in this study is the realization revenue of Groundwater Tax that did not reach the specified target. This lack of success on the Groundwater Tax revenue target is due to the lack of awareness of taxpayers in fulfilling their tax obligations. The purpose of this study was to analyze the effectiveness of groundwater tax revenue in an effort to increase local revenue along with the obstacles and efforts made by the Regional Revenue Agency in an effort to receive groundwater tax. This study used a descriptive qualitative research method. The location in this research was the Regional Revenue Agency of East Sumba Regency. In this study, the author used the theory of effectiveness according to Duncan that used three dimensions to measure effectiveness, i.e., goal achievement, integration, and adaptation. The results of this study showed that in 2018 and 2020 it was less effective because the effectiveness ratio was still below 80%, while in 2019 it was running very effectively as evidenced by the effectiveness ratio level being above 100%. This happens because of the lack of awareness of the taxpayer in paying the Groundwater Tax. The efforts made by the Regional Revenue Agency are to increase optimal supervision by monitoring and conducting socialization related to Groundwater Tax to Taxpayers.